Global, regional, and national burden of severe periodontitis, 1990–2019: An analysis of the Global Burden of Disease Study 2019 - Chen, Meng Xuan; Zhong, Yu Jie; Dong, Qian Qian; Wong, Hai Ming; Wen, Yi Feng (Journal of clinical periodontology, 2021)
Aim Up‐to‐date epidemiological studies on the global burden of severe periodontitis is scarce. This study aimed to present the latest estimates for prevalence of severe periodontitis from 1990 to 2019, by region, age, and level of socio‐demographic development. Materials and Methods Estimates from the Global Burden of Disease study 2019 were used to investigate burden and trends of prevalence of severe periodontitis and its association with socio‐demographic development at global, regional, and national level. Decomposition analysis was performed to explore the contribution of demographic and epidemiological factors to the evolving burden of severe periodontitis. Results In 2019, there were 1.1 billion (95% uncertainty interval: 0.8–1.4 billion) prevalent cases of severe periodontitis globally. From 1990 to 2019, age‐standardized prevalence rate of severe periodontitis increased by 8.44% (6.62%–10.59%) worldwide. Prevalence of severe periodontitis is higher among less developed countries/regions. Global population growth accounted for 67.9% of the increase in the number of prevalent cases of severe periodontitis from 1990 to 2019. Conclusions The global burden of severe periodontitis has been substantial and increasing over the past three decades. Upstream policy changes are urgently needed to address the global public health challenge of severe periodontitis.